2001
DOI: 10.1038/nn0901-927
|View full text |Cite
|
Sign up to set email alerts
|

Normal breathing requires preBötzinger complex neurokinin-1 receptor-expressing neurons

Abstract: The normal breathing rhythm in mammals is hypothesized to be generated by neurokinin-1 receptor (NK1R)-expressing neurons in the preBötzinger complex (preBötC), a medullary region proposed to contain the kernel of the circuits generating respiration. If this hypothesis is correct, then complete destruction of preBötC NK1R neurons should severely perturb and perhaps even fatally arrest breathing. Here we show that specific and near complete bilateral (but not unilateral) destruction of preBötC NK1R neurons resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
482
4
10

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(531 citation statements)
references
References 21 publications
35
482
4
10
Order By: Relevance
“…However, such techniques do not allow cellular-level quantitative analyses of lesion effects on behavior. Similarly, the toxin saporin causes graded cell destruction over several days, but it is impossible to keep a running tally of cell destruction in vivo while monitoring behavioral changes (5,6). We developed the present system for slices that retain behaviorally relevant function and expose CPG interneurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such techniques do not allow cellular-level quantitative analyses of lesion effects on behavior. Similarly, the toxin saporin causes graded cell destruction over several days, but it is impossible to keep a running tally of cell destruction in vivo while monitoring behavioral changes (5,6). We developed the present system for slices that retain behaviorally relevant function and expose CPG interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…The preBötzinger Complex (preBötC) of the medulla putatively contains the inspiratory CPG (3,4). Over several days in vivo, saporinmediated destruction of preBötC neurons that express neurokinin-1 receptors (NK1Rs) causes sleep-disordered breathing and fatal respiratory pathology (5,6). Similarly, acute cell-silencing of a subset of the same NK1R-expressing population of preBötC neurons stops spontaneous breathing in awake adult rats (7).…”
mentioning
confidence: 99%
“…Gray et al (6) demonstrated that Ͼ80% bilateral destruction of NK1R-expressing neurons was necessary to affect breathing and blood gases in awake rats. We previously demonstrated that 29% bilateral destruction of NK1R-expressing pre-BötzC area neurons in awake goats had minimal effect on arterial blood gases but caused transient alterations in breathing rhythm and/or pattern (26), and we reported here that 70% destruction of the pre-BötzC eliminates eupneic breathing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in vivo studies in anesthetized or decerebrate cats or rats demonstrate that lesioning of the pre-BötzC results in transient (24) or irreversible (7,10,18) elimination of eupneic respiratory activity. Further demonstrating the importance of the pre-BötzC in control of breathing was a study showing that Ͼ80% destruction of neurokinin-1 receptor (NK1R)-expressing neurons in the pre-BötzC resulted in an ataxic breathing pattern and hypoventilation in awake rats (6).…”
mentioning
confidence: 99%
“…Direct parallels of breath holding do not exist in other human behaviours but imaging studies of response inhibition during Go/NoGo and Stop-signal tasks (Aron and Poldrack, 2006;Liddle et al, 2001;Watanabe et al, 2002) and those related to inhibiting saccadic eye reflexes (Jueptner et al, 1996), highlight the dorsolateral prefrontal cortex, basal ganglia and thalamus as having a role in inhibiting behaviours. Within the brainstem, animal models have shown that stimulation of pontine respiratory neurones can lead to apnoea, hypernoea or apneusis (Chamberlin, 2004;Fung and St John, 1994;Mutolo et al, 1998), while ablation of the preBötzinger complex (preBötC), a small region of the ventrolateral medulla, can lead to central sleep apnoea and ataxic breathing during wakefulness (Gray et al, 2001;McKay et al, 2005) We hypothesised that breath holding would be associated with an inhibitory network of subcortical structures including the pons. We were aware that our subjects would experience secondary effects, such as interoceptive awareness and an increasing desire for, and an anticipation of, the subsequent breath; therefore, we also hypothesised activity within areas associated with respiratory awareness and air hunger, such as the insula and cingulate cortices (Banzett et al, 2000b;Evans et al, 2002;Peiffer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%